G73(P) The 'MoTHER' score – an evidence based assessment of predicting trainee confidence on return to work after maternity leave. (May 2019) - van Boxel, E; Mawson, I; Duncan, S; Dawkins, S; Fordham, J; van Boxel, G
Abstract : Introduction and aims: In 2014 the GMC published a review on the phenomenon of 'skills fade' during time out of practice. Although it recognized that skills fade is related to time out of training, it reported there was a lack of information available on specific risk factors. One common reason for time out of practice is maternity leave. Here we report the results of a national survey of paediatric trainees to investigate experiences of returning to clinical work after maternity leave with a view to establishing what specific factors affect confidence on return. Method: We conducted an online survey of doctors within the paediatric training programme (ST1–8) between March and May 2017. Trainees currently on maternity leave and those who had completed a period of maternity leave were invited to submit anonymous responses. Statistical analysis was performed to establish those factors that independently predicted confidence levels on return to work. Results: We received 146 responses across 12 deaneries. 120 of those respondents had returned to work. 95.8% reported an initial lack of confidence on returning to work lasting more than a week (36.7% more than 3 months). Analysis of the data revealed that the following were independent risk factors for experiencing a lack of confidence on return that continued beyond 1 month: taking more than 9 months maternity leave, working as a junior registrar (ST4–5), working part time, participating in work related revision less than once a month when out of programme and having a supervising consultant who was not aware of the trainees recent maternity leave. Conclusion: This work is the first to quantify what factors determine confidence on return to work following maternity leave. We propose a risk stratification score, the 'MoTHER' score, to predict those trainees that are likely to feel less confident on return to work. Trainees with a high MoTHER score could be targeted for extra support on return to work.